Human Right to Environment in Brazil: Democratic Access to Quality of Life and Dignity to Reach All? (Global Journal of Human-Social Science, 2019)
As an agent responsible for promoting sustainable development, the state has a role to contribute positively to an ecologically balanced environment, as this can act and interfere directly in the development and implementation of socioenvironmental policies. The environmental balance is one of the components of the desired sustainable development, it being included also a viable economy and a just society. The environment, in turn, must be understood as a fundamental part of the scope and enforcement of human rights, as the right to life, ecologically balanced environment and own sustainable development are key to the quality of life and the scope of the dignity of the human person. This work aims to show that the ecologically balanced environment and the quality of life of the social and environmental point of view is a human right and an obligation of the State, which should promote and provide it to the whole society.
Keywords: human rights; environment; environmental equity; sustainability